Diurnal variations in summertime lightning activity in Tropical Asia. (9th February 2013) - Sen Roy, Shouraseni; Balling, Robert C.
ABSTRACT Many meteorological phenomena exhibit distinctive diurnal variations that vary substantially from place to place. In this investigation, we use Tropical Rainfall Measuring Mission data to assess spatial patterns in the diurnal variations of summertime lightning activity throughout tropical Asia. Harmonic analysis of the dataset reveals strong diurnal patterns in lightning activity with most locations exhibiting an afternoon maximum and a late‐night, early morning minimum. Notable exceptions include the eastern coastal areas of the Indian subcontinent and China, with the peak activity occurring in the early evening hours. We generally find that the diurnal patterns are related to orographic interactions as well as the seasonal wind circulation of onshore winds along the coastal areas. The strength of the cycle was relatively stronger in the interior of the continent particularly over northwestern India and the Tibetan plateau. Copyright © 2013 Royal Meteorological Society